Effect of electrical parameters on the EDM performances of titanium alloy - Mohd Zahiruddin, Md. Zain; Erween, Abd. Rahim; Sulaiman, Hasan (Universiti Malaya (UM), 2011)
International Conference on Molecule-based Magnets (ICMM 2006) organized by University Malaya (UM), in association with the ASEAN University Network of Southeast Asia Engineering Education Development Network (AUN/SEED-Net), Standards and Industrial Research Institute of Malaysia (SIRIM), Federation of Malaysian Manufacturers (FMM) and ACA-Pacific Pte Ltd, 14th - 15th March at Midvalley Hotel, Kuala Lumpur.